Why to employ both migrants and natives? A study on task-specific substitutability - Anette Haas; Michael Lucht; Norbert Schanne (Journal for Labour Market Research, 2013)
This paper analyses the performance of migrants on the German labour market and its dependence on the tasks performed on their jobs. Recent work suggests quantifying the imperfect substitutability relationship between migrants and natives as a measure for the hurdles migrants have to face. Our theoretical framework adopts that migrant shares vary with qualification, task categories, and experience. Hence, substitution elasticities of an aggregate production function can be quite different regarding different job cells. Finally, we estimate elasticities of substitution for different aggregate CES-nested production functions for Germany between 1993 and 2008 using administrative data and taking into account the task approach. We find significant variation in the substitutability between migrants and natives across qualification levels and tasks. We show that especially interactive tasks seem to impose hurdles for migrants on the German labour market.
Keywords: J15; J24; J31; 330; Integrierte Arbeitsmarktbiografien; Einwanderer; Inländer; Substitutionselastizität; Ausländerbeschäftigung; berufliche Integration; Heterogenität; Tätigkeitsmerkmale; Bildungsniveau; Niedrigqualifizierte; Hochqualifizierte; manuelle Arbeit; geistige Arbeit; restriktive Arbeit; selbstbestimmte Arbeit; Arbeitsmarktchancen; ausländische Arbeitnehmer